Influence of social media applications on pre-service biology teachers’ learning outcomes in Kwara State college of education, Oro, Nigeria - Adeoye, Gabriel Ademakinwa; Adewumi, Gabriel Segun (Assimilation: Indonesian Journal of Biology Education, 2024)
This study examined the influence of social media applications on pre-service Biology teachers’ learning outcomes in Kwara State College of Education, Oro, Nigeria. The sample comprised sixty pre-service teachers who were drawn using purposive sampling technique from NCE 3 of the 2021/2022 set. Questionnaire was used for data collection while the data gathered were analyzed using mean, standard deviation and t-test statistical tool at a mean benchmark of 2.50. Findings from the study revealed that WhatsApp, Facebook, Instagram and YouTube are the commonly used social media applications by pre-service Biology teachers which are usually accessed through mobile phones and tablets. Further finding indicates that pre-service Biology teachers use social media applications daily but more during the night hours. There was also a significant difference between social media application usage and pre-service Biology teachers study habits in Kwara State College of Education, Oro, Nigeria t(118) = 2.39, p = .02. The study concluded that pre-service Biology teachers use social media and it is affecting their study habits, and in turn their learning outcomes. It is therefore, recommended that the college should provide adequate training to equip pre-service teachers with necessary skills to maximize the utilization of social media applications to boost their learning outcomes.